1993
DOI: 10.1034/j.1399-3054.1993.870204.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction and activation of the alternative oxidase of potato tuber mitochondria

Abstract: 1993. Induction and activation of the alternative oxidase of potato tuber mitochondria. -Physiol. Plant. 87: 134-141.Potato tubers (Sotanum tuberosum L. cv. Grata) were stored for at least 1 week at room temperature and then incubated with an equal amount of apples {Mains domestica L.) for 2 days. After this treatment, intact tuber mitochondria isolated by Percoll gradient centrifugation showed a high degree of induction of the alternative oxidase. measured as cyanide-resistant, salicylhydroxamic acid-sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0
1

Year Published

1993
1993
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 11 publications
2
14
0
1
Order By: Relevance
“…This is consistent with numerous studies on both isolated mitochondria and whole tissue that suggest that the AP is engaged in Oz consumption only when the CP becomes limiting or restricted (Theologis and Laties, 1978;Day and Lambers, 1983). It should be noted that partitioning between the two pathways may also be dependent on the substrates being oxidized by the mitochondria (Day et al, 1991;Wagner et al, 1992a), the level of potential allosteric activators of the AOX (Lidén and Akerlund, 1993;Millar et al, 1993), and possibly the oxidation state of an AOX sulfhydryl residue (Umbach and Siedow, 1993). More work is required to determine the significance of these regulatory mechanisms.…”
supporting
confidence: 67%
“…This is consistent with numerous studies on both isolated mitochondria and whole tissue that suggest that the AP is engaged in Oz consumption only when the CP becomes limiting or restricted (Theologis and Laties, 1978;Day and Lambers, 1983). It should be noted that partitioning between the two pathways may also be dependent on the substrates being oxidized by the mitochondria (Day et al, 1991;Wagner et al, 1992a), the level of potential allosteric activators of the AOX (Lidén and Akerlund, 1993;Millar et al, 1993), and possibly the oxidation state of an AOX sulfhydryl residue (Umbach and Siedow, 1993). More work is required to determine the significance of these regulatory mechanisms.…”
supporting
confidence: 67%
“…The very small concentrations of pyruvate needed to stimulate AOX (Fig. 1) and the high levels of ME in mitochondria from sweet potato (Table 11) and potato (Day et al, 1984) exacerbate this effect, especially when respiration is measured at acid pH, as was the case in the studies by Wagner et al (1989Wagner et al ( , 1995 and Lidén and Akerlund (1993). The latter authors recognized the need for succinate and malate to be metabolized to achieve their stimulating effect on AOX.…”
Section: Discussionmentioning
confidence: 82%
“…Succinate stimulated NADH oxidation even in the presence of the succinate dehydrogenase inhibitor malonate (Wagner et al, 1989;Lidén and Akerlund, 1993). Wagner et al (1989Wagner et al ( , 1995 showed that L-malate and its supposedly unmetabolized isomer, D-malate, stimulated AOX activity in potato callus mitochondria.…”
mentioning
confidence: 99%
“…An increase of the 02 uptake via the alternative pathway can be caused either by extra protein synthesis or by activation (via organic acids [13][14][15][16] and/or thiol modifications in the enzyme [17,18]). However, after 1 h in the presence of 10 mM H202, CN-resistant respiration was not different from the control cells (data not shown), indicating that extra protein synthesis and not activation of already existing protein is involved in the increase in activity.…”
Section: Sds-pa Ge and Immunoblottingmentioning
confidence: 99%
“…In this view, both the activation of the alternative pathway and induction of alternative oxidase gene expression contribute to the protection of the plant against active oxygen species. When substrate supply to the mitochondria is too high for the (impaired) cytochrome pathway, accumulating organic acids lower the K m of the oxidase for ubiquinol [13][14][15][16]18], and the increased activity of the pathway will prevent an increase of reduction levels of the respiratory components, which would lead to the formation of harmful active oxygen species. Whenever the (activated) capacity of the alternative oxidase is not sufficient and active oxygen species like H202 do accumulate, these products themselves induce the expression of extra alternative oxidase protein.…”
Section: Sds-pa Ge and Immunoblottingmentioning
confidence: 99%